The Influence of Business Development Strategies, Social Media Marketing, and Brand Image on Consumer Purchase Decisions with Consumer Trust as a Moderator - Muhammad Junaid Kamaruddin (Journal of Business and Behavioural Entrepreneurship, 2026)
This study aims to examine the influence of business development strategies, social media marketing, and brand image on consumer purchasing decisions, with consumer trust as a moderating variable. This research provides an in-depth understanding of how these three key factors affect consumer buying behavior, especially in the evolving context of digital marketing. Business development strategies, including product innovation, promotion, pricing, and distribution adjustments, are believed to enhance purchasing decisions with the support of consumer trust. Effective social media marketing through content creation and community building also plays a vital role in increasing brand awareness and consumer purchase intention. Furthermore, a positive brand image significantly boosts consumer trust and perception towards products, thereby encouraging purchasing decisions. The study employed a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) analyzed through SmartPLS software. The sample consisted of 150 respondents, with data tested for validity, reliability, and hypothesis testing. The results reveal that social media marketing, brand image, and consumer trust have a positive and significant impact on consumer purchasing decisions, whereas business development strategy does not have a direct effect. Consumer trust moderates the relationship between business development strategies and purchasing decisions but does not moderate the effects of social media marketing and brand image. These findings emphasize the importance of building consumer trust through effective digital marketing strategies to enhance purchasing decisions.